The executive disruption model of tinnitus distress: Model validation in two independent datasets using factor score regression - Clarke, Nathan A.; Akeroyd, Michael A.; Henshaw, Helen; Hall, Deborah A.; Mohamad, Wan Najibah Wan; Hoare, Derek J. (Frontiers in Psychology, 2023)
This study presents the Executive Disruption Model (EDM) of tinnitus distress and subsequently validates it statistically using two independent datasets (Construction Dataset: n=96 and Validation Dataset: n=200). The conceptual EDM was first operationalised as a structural causal model (construction phase). Then multiple regression was used to examine the effect of executive functioning on tinnitus-related distress (validation phase), adjusting for the additional contributions of hearing threshold and psychological distress. For both datasets, executive functioning negatively predicted tinnitus-distress score by a similar amount (Construction Dataset: β = -3.50, p = .13 and Validation Dataset: β = -3.14, p = .02). Theoretical implications and applications of the EDM are subsequently discussed; these include the predictive nature of executive functioning in the development of distressing tinnitus, and the clinical utility of the EDM.